PENGARUH PENERAPAN METODE CARD SORT TERHADAP MINAT BELAJAR PESERTA DIDIK KELAS TINGGI PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SDN 106 INPRES TAKALAR I - Artika Sari; B, Muhammad Rusmin; Salahuddin; Syahruddin; Muhammad Qasim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the low learning interest of students caused by boredom during the learning process. The research aimed to determine the implementation of the card sort method, students’ learning interest, and the effect of the card sort method on the learning interest of upper-grade students in Islamic Religious Education and Character subjects at SDN 106 Inpres Takalar I. This study employed a quantitative ex post facto approach with a simple paradigm design. The population consisted of 84 upper-grade students (grades IV, V, and VI), and all were selected as the sample using saturated sampling techniques. Data were collected through questionnaires and analyzed using descriptive and inferential statistical analysis. The results showed that the implementation of the card sort method had a positive effect on students’ learning interest. The statistical analysis indicated that tcount was greater than t_table (1.864 > 0.2146) with a significance level of 5%. The coefficient of determination showed that the card sort method contributed 41% to students’ learning interest, while the remaining 59% was influenced by other external factors. Therefore, the card sort method can be considered an effective and interactive learning strategy to improve students’ learning interest in Islamic Religious Education and Character subjects.